AN ANALYSIS OF MULTICULTURAL EDUCATION VALUES IN ENGLISH TEXTBOOKS OF MERDEKA CURRICULUM AT - Nurindah Purnama Sari; Murni Mahmud; Sahril (LP2M UIN Abdul Muthalib Sangadji Ambon, 2024)
This research aims to describe the values ​​of multicultural education in English textbooks at junior high school level. The data in this research is in the form of text that contains the value of multicultural education. The data source in this research is the English textbook for grade 7 and grade 8 of the Merdeka Curriculum. There are two data collection techniques used in this research, namely reading techniques and note-taking techniques. The data analysis technique in this research goes through three stages, namely (1) reduction, (2) presentation, and (3) drawing conclusions. Apart from that, data validity checking techniques were also carried out, namely discussions with experts in assessing the results of data analysis so that all findings in this research could be accounted for. The results of this research found that there are 7 values ​​of multicultural education, namely the values ​​of tolerance, justice or equality, respect for diversity, dialogue and cooperation, global perspective, empowerment, and intercultural understanding